Investigation of a Truncated Aptamer for Ofloxacin Detection Using a Rapid FRET-Based Apta-Assay - Sondes Ben Aissa; Mohamed Mastouri; Gaëlle Catanante; Noureddine Raouafi; Jean Louis Marty (Antibiotics, 2020)
In this work, we describe the use of a new truncated aptamer for the determination of ofloxacin (OFL), being a principal quinolone commonly used in both human and animal healthcare. Since the affinity of a 72-mer ssDNA sequence has been previously described without further investigations, this paper demonstrates the first computational prediction of the binding motif between this aptamer and OFL through in silico molecular docking studies. Besides, we suggest the application of the characterized recognition mechanism in a simple FRET (Förster Resonance Energy Transfer) pattern for the rapid aptasensing of the quinolone of interest. Accordingly, our approach harnesses the fluorescence quenching of the fluorescein-tagged aptamer (FAM-APT) induced by its partial hybridization to a tetramethyl rhodamine-labelled complementary ssDNA (TAMRA-cDNA). In such a structure, dye labels brought into close proximity act as a FRET pair. Upon ofloxacin addition, an affinity competition occurs to form a more stable FAM-APT/OFL complex, thus unquenching the FAM-APT signal. Interestingly, the recovered fluorescence intensity was found to correlate well with the antibiotic’s concentrations in the range of 0.2–200 μM in HEPES buffer, with a linear response that ranged between 0.2 and 20 μM. The rapid apta-assay achieved limits of detection and quantification of 0.12 and 0.40 μM, respectively. The truncated aptamer has also shown an improved specificity toward OFL than other quinolones, compared to the original full-length aptamer described in previous works. Finally, the practical application of the developed apta-assay was successfully confirmed to detect OFL quinolone in spiked milk samples, with satisfactory recoveries ranging between 97.4% and 111.4%.